Travel survey of residents of Canada, travel characteristics, by province of destination, 2011 - 2012 - Statistics Canada (Government of Canada, 2017)
This table contains 847 series, with data for years 2011 - 2012 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography, province of destination (11 items: Canada; Newfoundland and Labrador; Prince Edward Island; Nova Scotia; ...), Trip characteristics (40 items: Trip duration, total, same day and overnight trip; Trip duration, same day; Trip duration, overnight; Type of trip, non-residents trip; ...), Type of trip duration (2 items: Total trips; Overnight trips).